(NkWANTOWAQ HROMODINAMIKA (B:s (NwWEDENIE W TEORI@ KWARKOW I GL@ONOW (B: (NpER(B. (NS ANGL(B. /s - (NiNDURAJN(B, (Nf(B.s; (NbYKOW(B, (NaLEKSANDR aLEKSANDROWI^s ((NmOSKWA (B:s (NmIR(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 270-280s
Keywords: (NkWANTOWAQ HROMODINAMIKAs